Red-green-blue upconversion emission and energy-transfer between Tm3+ and Er3+ ions in tellurite glasses excited at 1.064 mu m - Amorim, H. T.; Vermelho, MVD; Gouveia-Neto, A. S.; Cassanjes, F. C.; Ribeiro, SJL; Messaddeq, Younes [UNESP] (Elsevier B.V., 2003)
Red, green, and blue emission through frequency upconversion and energy-transfer processes in tellurite glasses doped with Tm3+ and Er3+ excited at 1.064 mum is investigated. The Tm3+/Er3+-codoped samples produced intense upconversion emission signals at around 480, 530, 550 and 660 nm. The 480 nm blue emission was originated from the (1)G(4)-->H-3(6) transition of the Tm3+ ions excited by a multiphoton stepwise phonon-assisted excited-state absorption process. The 5 30, 5 50 nm green and 660 mn red upconversion luminescences were identified as originating from the H-2(11/2), S-4(3/2) --> I-4(15/2) and F-4(9/2) --> I-4(15/2) transitions of the Er3+ ions, respectively, populated via efficient cross-relaxation processes and excited-state absorption. White light generation employing a single infrared excitation source is also examined. (C) 2003 Elsevier B.V. (USA). All rights reserved.
Keywords: visible; fluorescence; upconversion; rare earth; glass; energy-transfer; white light